Nel, Philip, Was the Cat in the Hat Black? The Hidden Racism of Children’s Literature and the Need for Diverse Books, Oxford University Press, 2017 - Heywood, Sophie (Mémoires du livre / Studies in Book Culture, 2026)
This essay focuses on Philip Nel’s 2017 study Was the Cat in the Hat Black?, a landmark book in children’s literary and publishing studies. It demonstrates both the intellectual influence of critical race theory on contemporary thinking in the field, and bears witness to the intensification of attacks on the movement to promote children’s access to diverse books, and the scholarship that underpins it. In this presentation of his book, I set it in the context of research by scholars of colour and by white researchers such as Nel into the issue of racism in children’s books. Specifically, Nel’s book lays bare the unspoken white privilege that he argues structures so much of US-American children’s literature, and the “hidden racism” that it produces in children’s literature. Nel shows us how vast swathes of the English-language children’s literary canon is steeped in racist thought and traditions – including of course, Dr. Seuss’s iconic creation, The Cat in the Hat. The book’s recent reception history bears witness to the seismic shifts the newly-powerful and highly-organized extreme conservative right is causing the US children’s book world.